Pelvic inflammatory disease introduction - Pacheco Romero, José (2015)
We considered of great interest to the gynecologist the topic of pelvic inflammatory disease (PID), terminology used for infection of the endometrium, fallopian tubes and ovaries. The interesting thing about the disease is that the same bacteria that cause sexually transmitted infections (STIs) such as chlamydia, gonococcus, mycoplasma, and staph and estreptococo- cause about 90% to 95% of cases of PID. You could say that, as a result of an STI was AIDS, is the EPI. In addition to sexual contact, other ways that these germs enter the body include some cases of IUD insertion, childbirth, spontaneous abortion or electivo- both therapeutic and endometrial biopsy. We must keep in mind as risk factors of adolescent sexual activity, many couples, history of previous EPI, history of STIs and the use of oral contraceptives (when encourages the formation of ectropion).